2022
DOI: 10.3390/ijerph19148467
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Cardiovascular Diseases in Community Settings and Primary Health Care: A Pre-Implementation Contextual Analysis Using the Consolidated Framework for Implementation Research

Abstract: Cardiovascular diseases are the world’s leading cause of mortality, with a high burden especially among vulnerable populations. Interventions for primary prevention need to be further implemented in community and primary health care settings. Context is critically important to understand potential implementation determinants. Therefore, we explored stakeholders’ views on the evidence-based SPICES program (EBSP); a multicomponent intervention for the primary prevention of cardiovascular disease, to inform its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
1
3
0
1
Order By: Relevance
“…This may show that this type of intervention is particularly well suited to people with mental health concerns for whom talking to someone can make a real difference. This was also observed in the SPICES consortium partner sites including Brest (France) ( 58 ), and Antwerp (Belgium) ( 59 ). Most non-specialist or non-clinical people do not think of their health siloed into CVD, mental health, digestive health etc ( 60 ).…”
Section: Discussionsupporting
confidence: 53%
“…This may show that this type of intervention is particularly well suited to people with mental health concerns for whom talking to someone can make a real difference. This was also observed in the SPICES consortium partner sites including Brest (France) ( 58 ), and Antwerp (Belgium) ( 59 ). Most non-specialist or non-clinical people do not think of their health siloed into CVD, mental health, digestive health etc ( 60 ).…”
Section: Discussionsupporting
confidence: 53%
“…As prior research has also clearly demonstrated, public health initiatives and community driven measures can effectively promote healthy lifestyle practices. 20 The US Department of Health and Human Services therefore has an initiative 'Healthy People 2030' that is a data driven community-based health initiative to promote health and well-being in the next decade. 21 Our study, therefore, provides readers with the state-and county-level rates of CKM related premature aaCVM in the US.…”
Section: Discussionmentioning
confidence: 99%
“…Vol .7-N° 3, 2023, pp. 957-994 Journal Scientific MQRInvestigar 981 saludables, realizan ejercicio físico por un intervalo de 10-60 minutos a la semana y eliminan las grasas trans y saturadas (Reamy, Williams, & Kuckel, 2018), pero también existen otras medidas como programas de intervención (Aerts, Anthierens, Van Bogaert, Peremans, & Bastiaens, 2022), educación alimentaria (Mendoza Suárez, Concha Pazmiño, Cevallos Jaramillo, & Granda Alvarez, 2019), control de la presión arterial y del perfil lipídico (Avezum, y otros, 2018) y tratamiento de reducción de colesterol LDL con estatinas (Herdy, y otros, 2014). Estos resultados concuerdan con el estudio de Karunathilake y Ganegoda (Karunathilake & Ganegoda, 2018), que destaca las dietas, el ejercicio regular (30-60 minutos), el tratamiento con estatinas, cese completo del tabaco, restricción de grasas, educación sobre la enfermedad, mantener una presión arterial normal y llevar el control del perfil de lípidos como medidas de prevención ideales contra las ECV.…”
Section: Discussionunclassified